Why does the complexity of functionally equivalent signals vary across closely related species?. (17th June 2022) - Nelson, Claire M V; Sherwin, William B; Ord, Terry J
Abstract: Animal signals are observed to vary widely in complexity among species, but why this should be the case—especially among closely related taxa—is unclear. Identifying the selective forces that drive these differences is important for understanding signal evolution, as well as the origins of communication more generally. We used a measure derived from information theory to quantify the complexity of visual territorial advertisement displays performed by males of closely related taxa of Puerto Rican Anolis lizard. In general, the information potential of visual displays appeared to be high compared with signals of other taxonomic groups (e.g., other lizards, birds). Nevertheless, there was still considerable variation in signal complexity among the Anolis taxa studied. We found a strong relationship between signal complexity and phylogeny for some aspects of the advertisement display traditionally thought to be important in species recognition. Other aspects of the display tended to vary independently of phylogeny, with differences in signal complexity among taxa reflecting the distance over which displays were typically viewed by territorial neighbors, and to some extent the number of sympatric congeners present in the environment. More generally, we highlight a little used, but tractable means of quantifying complexity in different species—and in different aspects of the same signal (the number, timing, and type of components)—that can reveal the evolutionary processes generating increases (or decreases) in communicative complexity. Abstract : We measured the complexity of territorial displays performed by male anole lizards on the island of Puerto Rico. Displays were found to be highly complex, with variation among species the product of constraints on signal design and adaptations to local social environments. Our findings show why the same system of communication—here, used to advertise territorial ownership—can vary in complexity among closely related species, and helps reveal the origins of complexity more generally.